Use of Muscle Flaps in Burn Reconstruction - Abdullah, Sk Nishat; Das, Kishore Kumar; Hossain, Md Zakir; Awwal, Rayhana; Khondoker, Md Sazzad; Kalam, Md Abul (Bangladesh Journal of Plastic Surgery, 2014)
Electric burns are deep burns that by once-only or continuing stimulation of the nerves and striated muscles causes massive muscle contractions which can cause ruptures, ligamentous tears, fractures, and joint dislocations.High resistance of bone to the passage of electric current results in periosteal necrosis. Deep burns particularly electric burns when exposes structures valuable for important functions like joints, demands reconstructive options consisting robust viability and huge vascularity. The study was conducted in Department of plastic surgery and burn, Dhaka Medical College Hospital,Dhaka from June, 2011 to January, 2012. 18 patients were included in this series. Among them in ten patients gastrochnemius flap was applied, Lattissimus dorsi muscle flap was applied in 4 cases, Trapezius flap was applied in 2 cases and each of the other two patients were treated with Tensor fascia lata and Transverse Rectus Abdominis myocutaneous flap. Fifteen patients were adult and three patients were from paediatric age group. 88% of flaps were primarily used to cover exposed structures (bones and joints) and others were used to correct deformities. Complications include partial graft loss (3), joint stiffness(3), wound infection(1) and flap loss(1). Though these flaps are very commonly used in trauma reconstruction, their use in reconstruction in burn patients are included in this series. DOI: http://dx.doi.org/10.3329/bdjps.v4i1.18690 Bangladesh Journal of Plastic Surgery January 2013, 4(1): 29-31